AI and the Healthcare sector: Industry, legal and ethical issues - Dipla, Victoria (Bioethica, 2021)
In this modern era, AI systems, robotics and all kinds of technological innovations have prevailed in almost every industry there is. Even though, they provide with several advantages and benefits, such novelties, due to their newly found capacities pose a certain undoubted risk for contemporary societies, unfamiliar yet with the full extent of the perils following these kind of innovations. This article engages in an examination of one of the industries critically changed and influenceδ by AI technology, the healthcare industry, as it possesses the highest bioethical interest. The article, thus, is divided to four sections. The first is dedicated to novel advancements in the field of health care services and medicine, which include the introduction and/or full deployment of machine learning and robotics. Second, as already mentioned due to the fact that these technologies are accompanied by legal concerns, especially in terms of privacy, a legal analysis of the most relevant and prominent concerns is attempted. The emphasis is given on the European Union’s approach on the matter of AI related technology. Both its main bodies are mentioned, the European Parliament and the European Commission, for their procurement of documents related to novel technologies. In addition, after the legal framework analysis and the more binding in nature legislative efforts, the article proceeds with the presentation of the soft-law related to the AI technological field, as well as the ethics and guidelines developed to mitigate its risks and issues. Lastly, the following analysis is closed by conclusions based on the combination of remarks and resolutions from the above mentioned sections of the article.